Development of cement-bitumen composites for semi-flexible pavement surfacing - Koting, S.; Karim, M.R.; Mahmud, H.; Abdul Hamid, N.A. (2011)
Cement-bitumen composites are produced by pouring selected cementitious grout slurries onto the surface of open graded asphalt skeletons, which subsequently filled the voids under the influence of gravitational action. The main objective of this study is to investigate the mechanical properties of cement-bitumen composites as an alternative semi-flexible pavement surfacing material. This involves the selection of acceptable proportions of cementitious grouts as well as the development of satisfied grouted pavement mixes. The cementitious grout mixtures, open graded asphalt skeletons and grouted pavement mixes were tested for physical, strength and deformation performances.